Edukasi Pentingnya Penggunaan Sunscreen pada Kalangan Remaja di SMA Islam Sabilillah Malang - Elva Asmiati; Rizka Novia Atmadani; Fitria Dwi Damayanti; Risma Ayu Setiawan (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of this community service is to provide the students knowledge about the benefits and importance of using sunscreen in everyday life. Based on the several steps of the method we used, starting from the preparation of the event, pre-test before giving the material, then giving the material through Power-point slides, post-test evaluation, and closing. Partners in this service are students at Sabilillah Islamic High School Malang. The instrument in giving the material is power point and to do the pre-test and post-test using the google form platform. The results of this service is an increase in the knowledge of the students at Sabilillah Islamic High School MalangÂ  which can be seen in the pre- and post-test scores of respondents' knowledge of the material provided. The value shows an increase from before and after the provision of material which indicates that the provision of education has succeeded in increasing knowledge for students at Sabilillah Islamic High School Malang.